Foundation Flash Applications for Mobile Devices - Leggett, Richard; De Boer, Weyert; Janousek, Scott (Apress : Imprint: Apress, 2007)
With a growing number of mobile devices offering Flash support, it is an increasingly viable platform for the development of mobile applications. Foundation Flash Applications for Mobile Devices is just the book you need to learn how to take advantage of this new audience of mobile application users. Inside, it covers every facet of mobile Flash, from the essentials of the Flash Lite 1.1 and 2.X platforms and writing applications to testing your work and deploying to mobile users. Applications presented include screensavers, wallpapers, data-consuming informational programs (such as movie, news, and stock tickers), quiz games, action games, and more. You are given tips on mobile Flash development best practices, and all of the essential topics are covered, including creating and using sound, vector graphics, and bitmaps; optimizing assets for the small screen; coding realistic physics for games; and consuming web services using PHP, Java, ColdFusion, and .NET. Throughout the book, there are many samples to put together and learn from, and several bonus applications are also available to download and check out.